2006
DOI: 10.1080/09658210600759733
|View full text |Cite
|
Sign up to set email alerts
|

Event components in autobiographical memories

Abstract: Autobiographical memories contain activity, location, temporal, and participant information (Lancaster & Barsalou, 1997). Our study analysed potential dominance of activity information in autobiographical memories. The results indicated stability in dominance of the activity component, defined as similar occurrence in first and subsequent reports, and a relative absence of the temporal component in these verbal reports. Activity dominance also occurred when activity information from the verbal reports was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…As predicted, a location cue was more effective at eliciting accurate alibis than was a time cue. This result is not surprising; previous findings also indicate that time cueing is generally ineffective compared with location cueing (e.g., see Brewer, ; Dijkstra & Misirlisoy, ; Wagenaar, ). What is surprising, however, is the low accuracy rate of the paired cue.…”
Section: Discussionsupporting
confidence: 59%
“…As predicted, a location cue was more effective at eliciting accurate alibis than was a time cue. This result is not surprising; previous findings also indicate that time cueing is generally ineffective compared with location cueing (e.g., see Brewer, ; Dijkstra & Misirlisoy, ; Wagenaar, ). What is surprising, however, is the low accuracy rate of the paired cue.…”
Section: Discussionsupporting
confidence: 59%
“…The effect of retrieval support on autobiographical memory recall with cues (who, what, where, when) taken from the original report has been demonstrated to aid the recall of the remainder of the memory in studies with young adults (Burt, 1992), older adults (Catal & Fitzgerald, 2004), and both young and older adults (Dijkstra & Misirlisoy, 2006;Kristo et al, 2009). These studies demonstrated better performance with the what retrieval cue than with other retrieval cues (Burt, 1992;Catal & Fitzgerald, 2004), equal facilitation of the what and who cue (Dijkstra & Misirlisoy, 2006;Kristo et al, 2009), and better performance with multiple cues than with one retrieval cue (Wagenaar, 1986). Together, these findings support the idea that retrieval cues may help reinstate access to details of the original experience, and hence, support accurate retrieval of the memory and its details.…”
Section: Cued Recallmentioning
confidence: 99%
“…Moreover, what cues were expected to be more successful than other cues, because they contribute more to the reconstruction of the original experience (the event itself) than where and who cues (Burt, 1992;Catal & Fitzgerald, 2004). The when cue was not included in the study, because earlier findings have shown that this retrieval cue is not helpful (Dijkstra & Misirlisoy, 2006).…”
Section: The Present Studymentioning
confidence: 99%
“…She often talked about "confusing the poor little pillbox" when she does something that is not typical of routine. Time or a date is a typically poor memory cue [5]. Often calendars (electronic or paper) can be a good source of memory cues.…”
Section: Intention To Be More Consistentmentioning
confidence: 99%